Comparison of Ho:YAG laser and pneumatic lithotripsy in the treatment of impacted ureteral stones: An analysis of risk factors. Issue 3 (21st September 2013) - Degirmenci, Tansu; Gunlusoy, Bulent; Kozacioglu, Zafer; Arslan, Murat; Koras, Omer; Arslan, Burak; Minareci, Suleyman
Abstract: The aim was to compare pneumatic and holmium:yttrium‐aluminum‐garnet laser in the treatment of impacted ureteral stones with different locations and to identify the risk factors for complications. Between March 2005 and November 2012, a total of 230 patients underwent ureteroscopic lithotripsy for impacted stones. Of the patients, 117 had pneumatic and 113 had laser lithotripsy for the fragmentation of the stones. Treatment outcomes based on evidence of being stone free were evaluated. Preoperative, operative, and postoperative follow‐up findings were analyzed and compared. There was a difference between the two groups according to overall stone clearance rate (93.8% vs. 80.3%, p  = 0.002). There was no statistically significant difference for distal location between the laser and pneumatic groups (96.8% vs. 91.7%, p  = 0.288). For 10 patients with intrarenally migrated stones who were managed with flexible ureterorenoscopy in the same session, laser lithotripsy was more successful than pneumatic for proximal ureteral stone (94.4% vs. 67.9%, p  = 0.007). The overall complication rate was 26.1%. There was no statistically significant difference between the two groups (29% vs. 23%, p  = 0.296). Multivariate logistic regression analysis revealed that the proximal location was a statistically significant parameter for the occurrence of complications in both groups ( p  = 0.001 for PL, p  = 0.004 for laser). The pneumatic and holmium:yttrium‐aluminum‐garnet laser lithotripsy are effective in the treatment of distal impacted stones. Both treatments with semirigid ureteroscopy are acceptable for proximal impacted ureteral stones, but holmium laser lithotripsy has an advantage of use with flexible ureteroscope for intrarenally migrated stone.